Effects of Technology Transfer on Malaysian-Based Electronic Firms - Suntharalingam, Chubashini (1999)
This study was carried out to determine effects of technology transfer on Malaysian-based electronic firms by examining whether the factors found to be inherent (i.e. corporate culture, organisational structure and system, skills, language, flow of communication, attitude and behaviour of manager and employee, and transfer of personnel) in technology transfer in the West were applicable in the technology transfer process in Malaysian firms. The study focused on two types of firms, which were electronic-based, i.e. Japanese and American firms. Investigations were also made to elucidate the influence of information technology (IT) on technology transfer.Data for this study were obtained through personal interviews, structured questionnaire and secondary sources. Results showed that the inherent factors operating in the technology transfer process in Malaysia were in conformity with those found in technology transfer processes occurring in the West. Comparatively, it was found that the Japanese firms underwent more intense changes in their organisational aspect in order to adopt new technologies. The American firms, on the other hand, were found to be agreeable to the notion that IT influenced the technology transfer process. This was because the Americans were more exposed to the usage of IT in the said area as compared to the Japanese. This study showed that human and organisational aspect of a firm were important in ensuring successful implementation of new technologies in the respective firms. However, further research should be carried out to determine the degree of importance of the inherent factors, which are responsible in ensuring successful technology transfer.